Impact of HPMCAS on the Dissolution Performance of Polyvinyl Alcohol Celecoxib Amorphous Solid Dispersions - Marius Monschke; Karl G. Wagner (MDPI AG, 2020)
Amorphous solid dispersions (ASDs) have been proven to increase the bioavailability of poorly soluble drugs. It is desirable that the ASD provide a rapid dissolution rate and a sufficient stabilization of the generated supersaturation. In many cases, one polymer alone is not able to provide both features, which raises a need for reasonable polymer combinations. In this study we aimed to generate a rapidly dissolving ASD using the hydrophilic polymer polyvinyl alcohol (PVA) combined with a suitable precipitation inhibitor. Initially, PVA and hydroxypropylmethylcellulose acetate succinate (HPMCAS) were screened for their precipitation inhibitory potential for celecoxib in solution. The generated supersaturation in presence of PVA or HPMCAS was further characterized using dynamic light scattering. Binary ASDs of either PVA or HPMCAS (at 10% and 20% drug load) were prepared by hot-melt extrusion and solid-state analytics were conducted using differential scanning calorimetry (DSC), X-ray powder diffraction (XRPD) and fourier-transformed infrared spectroscopy (FT-IR). The non-sink dissolution studies of the binary ASDs revealed a high dissolution rate for the PVA ASDs with subsequent precipitation and for the HPMCAS ASDs a suppressed dissolution. In order to utilize the unexploited potential of the binary ASDs, the PVA ASDs were combined with HPMCAS either predissolved or added as powder and also formulated as ternary ASD. We successfully generated a solid formulation consisting of the powdered PVA ASD and HPMCAS powder, which was superior in monophasic non-sink dissolution and biorelevant biphasic dissolution studies compared to the binary and ternary ASDs.